2016
DOI: 10.2903/j.efsa.2016.4545
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of titanium dioxide (E 171) as a food additive

Abstract: The present Opinion deals with the re-evaluation of the safety of titanium dioxide (TiO 2 , E 171) when used as a food additive. From the available data on absorption, distribution and excretion, the EFSA Panel on Food Additives and Nutrient Sources added to Food concluded that the absorption of orally administered TiO 2 is extremely low and the low bioavailability of TiO 2 appears to be independent of particle size. The Panel concluded that the use of TiO 2 as a food additive does not raise a genotoxic concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(76 citation statements)
references
References 141 publications
(282 reference statements)
2
73
0
1
Order By: Relevance
“…Certain rutile grades of titanium dioxide are produced using potassium aluminum silicate (also known as mica) as a template to form a basic platelet structure [2] and are generally referred to as pearlescent pigments [3]. The application of E171 in food was subjected to a (re-)evaluation by the European Food Safety Authority (EFSA) in 2016 [4] and was re-approved for use in food. It is commonly applied in confectionery (including candies, chewing gum, glazings) but was demonstrated also in pastries, low-fat dairy products, and sauces [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain rutile grades of titanium dioxide are produced using potassium aluminum silicate (also known as mica) as a template to form a basic platelet structure [2] and are generally referred to as pearlescent pigments [3]. The application of E171 in food was subjected to a (re-)evaluation by the European Food Safety Authority (EFSA) in 2016 [4] and was re-approved for use in food. It is commonly applied in confectionery (including candies, chewing gum, glazings) but was demonstrated also in pastries, low-fat dairy products, and sauces [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Many consumers are exposed to food containing E171 on a daily basis [4,6,[10][11][12][13]. Among the different routes of exposure, the oral uptake route remains the least documented [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In September 2016, EFSA published an opinion on the re-evaluation of E171, based on a detailed literature review on TiO 2 nanoparticles. It was concluded that current exposure of consumers to E171 related to its use in foodstuffs is not likely to constitute a health risk, but that it was not possible to establish an acceptable daily intake [43].…”
Section: Titanium Dioxide (Tio 2 )mentioning
confidence: 99%
“…Titanium dioxide was actually identified in chewing gums [1][2][3], confectionary [4,5], sauces and dressings [5], non-dairy creamers [2,5] and in dietary supplements [6]. According to a database collecting the details of new products (278,705) introduced on the market in 62 of the world's major economies, the use of TiO 2 increased constantly until 2014, representing a labelling on more than 3500 foods or drinks (Mintel GNPD database cited by the European Food Safety Agency EFSA [7]). If TiO 2 is found in only 1.3% of new products, it is nevertheless found in 51% of gums, 25% of stick, liquid and sprays, 21% of mixed assortments, 10% of pastilles, gums, jellies and chews and 10% of lollipops [7].…”
Section: Food Categories With Permitted Use Of Tiomentioning
confidence: 99%